2018
DOI: 10.1111/aogs.13511
|View full text |Cite
|
Sign up to set email alerts
|

Childhood health and education outcomes following early term induction for large‐for‐gestational age: A population‐based record linkage study

Abstract: Introduction:There is debate about optimal management of pregnancies with a large-for-gestational age baby. A recent randomized controlled trial reported that early term induction of labor reduced cesarean section rates and infant morbidity. However, long term childhood outcomes have not been assessed. The aim of this study was to assess maternal, neonatal and child health and education outcomes for large-for-gestational age babies induced at 37-38 weeks' gestation. Material and methods:Population-based record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…There is also concern about the short- and long-term adverse effects of iatrogenic early term births. Being born at 37–39 weeks’ gestation, as opposed to > 40 weeks, is associated with a higher rate of immediate perinatal morbidity, hospitalisation in the first five years of life, childhood diabetes, and impaired primary school performance 28 , 29 . Whether earlier birth in SA-born women reduces adverse outcomes without causing harm is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…There is also concern about the short- and long-term adverse effects of iatrogenic early term births. Being born at 37–39 weeks’ gestation, as opposed to > 40 weeks, is associated with a higher rate of immediate perinatal morbidity, hospitalisation in the first five years of life, childhood diabetes, and impaired primary school performance 28 , 29 . Whether earlier birth in SA-born women reduces adverse outcomes without causing harm is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[30,31] Other longitudinal studies of IOL for LGA also demonstrated signi cantly reduced birthweight in the IOL cohorts compared to expectant management associated with increased hospitalisations and special needs to age 8 years. [32] Across the 20 year study period the rate of intrapartum CS remained relatively stable in both nulliparous and multiparous women. This suggests that the increase in CS reported in both Queensland and national perinatal data are related predominantly to non-labour CS.…”
Section: Population Demographicsmentioning
confidence: 95%
“…This gestational age has been chosen to minimize iatrogenic prematurity, and a later gestational age would not reduce the neonatal morbidity that is intended to be reduced. A population-based study [28] reported on infant health and educational outcomes in 412 children born after labor induction between 37 and 38 weeks for LGA (birth weight >95th percentile) compared to 9762 children managed with expectant management, with a follow-up period of 9 years. The study revealed that children in the first group subjected to labor induction had a higher number of low Apgar scores, birth trauma, neonatal jaundice, phototherapy use, and neonatal intensive care unit admission, and as children, they had higher hospitalization and admission rates (RR 1.16; 95% CI: 1.04-1.30) and special needs (RR 1.98; 95% CI: 1.12-3.50).…”
Section: When To Perform Labor Inductionmentioning
confidence: 99%